THINKING ON THE CHANGING REPRESENTATION OF MUSIC ON CYBERSPACE - GÜVEN, Uğur Zeynep (Cyberpolitik Journal, 2017)
This paper addresses the emerging concept of cyberization of music through a particular focus on the changing representation of music. In this context, the first part presents a historical overview on the representation of music for a better understanding of today’s digitalization of music. The second part revolves around the intertwining relationship between technology and society and its impact on cultural preferences and taste in music. The last part focuses particularly on the emerging concept of cyberization of music and questions the ways it transformed the musical representation. The evaluations expose an ever-changing musical representation in our contemporary era, with a lack of live interaction where music followers tend to be influenced by the shared view of the others. Since there is no single and absolute correct way of analyzing the cyberspace for it has become an overarching term used to describe a multitude of aspects of the new communication technologies, the evaluations herein wishes to contribute to the interpretation of music on cyberspace.